Electrochemical Stability of the Reconstructed Fe3O4(001) Surface. (29th September 2020) - Grumelli, Doris; Wiegmann, Tim; Barja, Sara; Reikowski, Finn; Maroun, Fouad; Allongue, Philippe; Balajka, Jan; Parkinson, Gareth S.; Diebold, Ulrike; Kern, Klaus; Magnussen, Olaf M.
Abstract: Establishing the atomic‐scale structure of metal‐oxide surfaces during electrochemical reactions is a key step to modeling this important class of electrocatalysts. Here, we demonstrate that the characteristic (√2×√2)R45° surface reconstruction formed on (001)‐oriented magnetite single crystals is maintained after immersion in 0.1 M NaOH at 0.20 V vs. Ag/AgCl and we investigate its dependence on the electrode potential. We follow the evolution of the surface using in situ and operando surface X‐ray diffraction from the onset of hydrogen evolution, to potentials deep in the oxygen evolution reaction (OER) regime. The reconstruction remains stable for hours between −0.20 and 0.60 V and, surprisingly, is still present at anodic current densities of up to 10 mA cm −2 and strongly affects the OER kinetics. We attribute this to a stabilization of the Fe3 O4 bulk by the reconstructed surface. At more negative potentials, a gradual and largely irreversible lifting of the reconstruction is observed due to the onset of oxide reduction. Abstract : In situ and operando X‐ray diffraction shows that the surface reconstruction of magnetite single crystals, formed in vacuum, persists under harsh oxygen evolution reaction conditions and protects the bulk magnetite from further oxidation. It also alters the catalytic properties with respect to the unreconstructed surface. The reconstruction is irreversibly lifted upon reduction of surface iron cations.